Letter : Basque Children - Ferguson, T. M.
1941-01-21 038-0035-001 Telephone No. 5273 Dundee and District Union of Jute and Flax Workers Affiliated with the General Federation of Trade Unions and the British and Scottish Trades Union Congresses T.M. FERGUSON Secretary In reply please quote Ref. - 69/71 NETHERGATE, DUNDEE 21st January 1941. The Secretary, Trades Union Congress, Transport House, Smith Square, LONDON. S.W.1 Dear Sir, BASQUE CHILDREN. With further reference to your letter of 1st January 1941, which was before my Executive Committee at their meeting held on 19th inst. I am desired to forward the enclosed cheque for Fifty Pounds (£50) as a donation to the International Solidarity Fund to be specially used for the maintainence of the Basque children. Please acknowledge with official receipt and oblige. Yours faithfully. T M Ferguson Secretary. Miss Cobbett £50 PTO 292/946/38/35(I)